BENTUK KETERLIBATAN PEMEGANG SAHAM DALAM PERBUATAN MELAWAN HUKUM PERSEROAN TERBATAS YANG DAPAT MEMPERLUAS PERTANGGUNGJAWABANNYA - Velliana Tanaya (Fakultas Hukum, Universitas Pelita Harapan | Lippo Karawaci, Tangerang, 2018)
Limited Liability Company is the most popular form of business entity in Indonesia because law acknowledges the principle of limited liability of its shareholders, which gives advantages for entrepreneurs running a business. Article 3 Subsection 1 Law No. 40 Year 2007 concerning Limited Liability Company stated that company’s shareholders are not personally liable for agreements made on behalf of the Company and are not liable for the Company’s losses in excess of their prospective shareholding. However, in Article 3 Subsection 2 there are some waivers of the principle, one of the exceptions is if the relevant shareholders are involved in illegal actions committed by the Company. It is interesting because in fact, usually, shareholder do not get involved in company’s management. Through normative research with Statute and Conceptual Approach on Piercing the Corporate Veil, shareholders can be accountable for personal responsibility if shareholders in giving his/her voting rights in General Meeting of Shareholders neglect his/her duty of care, or if besides of being shareholders he/she also become Board of Directors and/or Board of Commissioners who runs the Company’s management, or if the shareholders give order or command to Board of Directors or Board of Commissioners or company’s employee to perform actions that causing the Company committed an unlawful act and harm others (tort). Personal liability can be requested if injured party filing a tort lawsuit and set the relevant shareholders as a defendant besides the Company.